2007
DOI: 10.1029/2007jd008670
|View full text |Cite
|
Sign up to set email alerts
|

Urban photochemistry in central Tokyo: 1. Observed and modeled OH and HO2 radical concentrations during the winter and summer of 2004

Abstract: [1] We used laser-induced fluorescence to measure the concentrations of OH and HO 2 radicals in central Tokyo during two intensive campaigns (IMPACT IVand IMPACT L) in January-February and July-August 2004. The estimated detection limit for the 10-min data was 1.3 Â 10 5 cm À3 for the nighttime and 5.2 Â 10 5 cm À3 for the daytime. The median values of the daytime peak concentrations of HO 2 were 1.1 and 5.7 pptv for the winter and summer periods, respectively, while the values for OH were 1.5 Â 10 6 and 6.3 Â… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
288
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(334 citation statements)
references
References 40 publications
34
288
1
Order By: Relevance
“…They obtained a mean concentration of 0.5 ppb at noontime (11:00-14:00 LT). The observed HONO daytime concentration fell within the range of the previous observations in urban areas and megacities worldwide, 0.05-2.0 ppb (Alicke et al 2002;Acker et al 2006;Hao et al 2006;Kanaya et al 2007;Elshorbany et al 2009;Qin et al 2009). …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…They obtained a mean concentration of 0.5 ppb at noontime (11:00-14:00 LT). The observed HONO daytime concentration fell within the range of the previous observations in urban areas and megacities worldwide, 0.05-2.0 ppb (Alicke et al 2002;Acker et al 2006;Hao et al 2006;Kanaya et al 2007;Elshorbany et al 2009;Qin et al 2009). …”
Section: Resultssupporting
confidence: 82%
“…For comparison, the field measurement conducted by Hao et al (2006) in October 2004 to January 2005 at the same location led to daytime and nighttime HONO/NO 2 ratios of 0.022 and 0.058, respectively. The obtained HONO/NO 2 ratios were in line with those observed in many urban areas in the world during daytime (HONO/NO 2 = 0.003-0.075) and nighttime (HONO/NO 2 = 0.025-0.175) measurements (Alicke et al 2002;Acker et al 2006;Hao et al 2006;Kanaya et al 2007;Elshorbany et al 2009;Qin et al 2009;Tong et al 2015).…”
Section: Time Series Of Hono No 2 and Hono/no 2 Ratiosupporting
confidence: 87%
“…Observations of OH and HO2 in the urban atmosphere have primarily been 5 made using fluorescence assay by gas expansion (FAGE), and comparisons with predicted radical concentrations using chemistry box models constrained with co-located radical precursor measurements have revealed varying levels of success in replicating observations. Radical concentrations have been reported to be under-predicted by models (Ren et al, 2003;Martinez et al, 2003;Emmerson et al, 2005a;Chen et al, 2010;Lu et al, 2012;Lu et al, 2013), over-predicted (George et al, 1999;Konrad et al, 2003;Dusanter et al, 2009) and, at times, models and measurements have been reported to be in 10 reasonable agreement, to within 40%, (Shirley et al, 2006;Emmerson et al, 2007;Kanaya et al, 2007;Sheehy et al, 2010;Elshorbany et al, 2012;Ren et al, 2013;Griffith et al, 2016). Often the level of agreement observed was found to be dependent on time of day (Brune et al, 2016); with poorest agreement between modelled and measured OH concentrations generally observed during the night.…”
Section: Introductionsupporting
confidence: 51%
“…Ozonolysis reactions have been reported as important primary radical sources during a number of studies, for example 25 these reactions accounting for 67% of the OH initiation in Birmingham during the PUMA campaign in winter (Emmerson et al, 2005b) whilst in Tokyo during the IMPACT campaign ozonolysis reactions were the dominant radical source during the night-time in winter (Kanaya et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation